Effects of phosphorus on loosely bound and tightly bound extracellular polymer substances in aerobic granular sludge - Yan, L. L. (Array, 2019)
The stability of aerobic granular sludge (AGS) is closely related to its extracellular polymeric substances (EPS). In this study, the composition and physicochemical characteristics of EPS in AGS were determined to evaluate their roles in AGS stability. The study evaluated the influence of influent phosphorus concentration on EPS protein (PN), polysaccharide (PS) and orthophosphate content, zeta potential (ζ) and fluorescence spectrum (EEM) in loosely bound EPS (LB-EPS) and tightly bound EPS (TB-EPS). With higher influent phosphorus concentration, the PN, PS and orthophosphate content were higher, as was the zeta potential in TB-EPS, but it had less influence on LB-EPS. Three-dimensional, synchronous fluorescence spectroscopy and fluorescence region integral (FRI) showed that protein-like substances were the primary components of LB-EPS and TB-EPS. Phosphorus had a dynamic quenching effect on EPS at a concentration between 0 mg L–1 and 17.5 mg L–1, which is the indirect production of phosphorus by cations. An increased concentration of influent phosphorus was beneficial to AGS stability.